Search for 2β processes in ¹⁰⁶Cd with ¹⁰⁶CdWO₄ crystal scintillator - Polischuk, O.G.; Belli, P.; Bernabei, R.; Brudanin, V.B.; Cappella, F.; Caracciolo, V.; Cerulli, R.; Chernyak, D.M.; Danevich, F.A.; D'Angelo, S.; Incicchitti, A.I; Laubenstein, M.; et al. (Functional Materials, 2015)
An experiment to search for double β (2β) decay of ¹⁰⁶Cd with the help of a low-background cadmium tungstate crystal scintillator developed from cadmium enriched in ¹⁰⁶Cd to 66 % (106CdWO4, 215 g) is in progress at the STELLA facility of the Gran Sasso underground laboratory (INFN, Italy). The ¹⁰⁶CdWO₄ scintillator is viewed by low-background photomultiplier through a PbWO₄ crystal light-guide produced from deeply purified archaeological lead. The detector operates in coincidence with the four low-background HPGe detectors to search for 2β processes with the emission of gamma quanta. Sensitivity of the experiment after 10678 h of data taking to different channels of 2β decay of ¹⁰⁶Cd is on the level of limT₁/₂ ~ 10¹⁹-10²¹ years.